Decision Making Styles Among Learners of The Faculty of Education At Tishreen University/A Feild Study At Tishreen University - حمدان ميساء (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The Purpose Of The Current Research Was To Determine The Decision – Making Styles Of The Learners Of The Faculty Of Education At Tishreen University. The Research Made Use Of The Descriptive Approach Which Was Based On Measuring Decision – Making Styles Of The Learners Of The Faculty of Education At Tishreen University. The Research Sample Was Stratified Random Comprised Of (300) Learners From The Faculty Of Education At Tishreen University. To Achieve The Objectives Of The Research, Scale Tool Designed By The Researcher Sajan Al-Milhem Was Used Which Consisted Of (42) Items Is Sub-Divided Into (3) Domains Represent Decision-Making Styles. The Validity and Stability Tool Had Been Verified And Established, The Results Revealed That All The Decision -Making Styles Like Deliberation, Hasty, And Frequency Were Being Practiced By The Learners Regardless Any Discrimination Due to Scientific Specializations With Minor Differences. It Was Also Found That There Was No Significant Difference In The learner’s Use Of Frequency Decision-Making Style. The Difference Which Subsists Was That Deliberation and Haste Decision-Making Styles Were Better Among Curricula And Education Methods Department Students, In Addition To Decision-Making Styles As a Whole. And To Achieve Deep Understanding For The Fennomen There Were Some Suggestions Such As. Qualitative Studying To The Relationship Between The Decision – Making Styles Of The Learners And The Situations Which Are Needed The Decision – Making.